Pengaruh Literasi Keuangan Syariah dan Persepsi Risiko Terhadap Minat Investasi Emas Generasi Milenial Muslim di Jabodetabek - Muhammad Faraghy Hasan; Dedy Rachmad (Department Islamic Economics, 2024)
The Effect of Sharia Financial Literacy and Perception of Risk on Muslim Millennials' Gold Investment Interest In Jabodetabek using the theory planned behavior approach). The data used in this study consisted of primary and secondary data collected through a quantitative approach to answer the problem under study. primary data obtained directly from sources using a questionnaire and using SEM-PLS analysis. Sharia Financial Literacy, Attitudes, Subjective Norms and Risk Perceptions have a positive and significant influence on gold investment interest while Perceived Behavioral Control has no influence on gold investment interest. The limitations of this study are the limited number of millennial respondents who became the research sample, namely only respondents who live in Jabodetabek and the interest in gold investment used in this study is still general. This research adds to the literature in gold investment interest which is still rarely discussed, this research uses a planed behavioral theory approach and adds to the variables of Islamic financial literacy and risk perception in gold investment interest, this research can also contribute to the literature on why the Jabodatabek Muslim community has an interest in investing in gold.